3D Robot Model Development - Maksymova, S.; Yevsieiev, V.; Demska, N. (Technical science research in Uzbekistan, 2023)
Modeling robots, their design and movement is an urgent task. Such modeling allows us to anticipate and solve many problems that arise both during the physical creation of the robot and during its operation. This article proposes a three-dimensional modeling of the robot – the MP-999E hand. First, the process of modeling a gear wheel is discussed in detail, and then the modeling of the robot itself.
Keywords: 3D model; Robot; Prototype; Spur gear; Gear tooth